Evaluation of Telemedicine Services in Outpatient Services at Hospital X, Jember District using the Human Organization Technology Method (Hot-Fit Model) - Niken Wahyu Puspitarini; Nuryadi Nuryadi; Saiful Bukhori (GLOBAL HEALTH SCIENCE GROUP, 2025)
The use of telemedicine as an information technology innovation in health services is one of the important strategies in improving quality services, especially in the era of digitalization of the health system. This study aims to capture patient perceptions and satisfaction with the use of telemedicine services at the X Hospital using the HOT-Fit Model approach. This study uses a quantitative method with a cross-sectional design and SmartPLS-based Structural Equation Modeling (SEM) analysis, involving 380 randomly selected respondents. Data was collected by filling out a questionnaire via Google Form. The results of the study indicate that there is a significant relationship between human, organizational, and technological variables on the net benefits or utilization of telemedicine. The technological factor has the most dominant influence both directly on utilization and indirectly through improving the quality of human resources and organizational support. These findings emphasize the importance of investing in technological infrastructure, increasing digital human resource literacy, and the role of organizations in supporting the successful implementation of telemedicine services.